SECULARISM, SECULARIZATION AND MINORITISATON - Parekh, Bharathi G (Journal of Dharma, 2000)
It was when I was reading article "A Way of Life" by P.R. Ram in the Economic and Political Weekly, (a Sameeksha Trust Publication), Vol. XXXI No.9, (1996), pp.519ff. on the Supreme Court judgment 'Hindutva and Hinduism, I was prompted to think on the secularism of our country. Hindutva and Hinduism are related to a way of life rather than to narrow limits of religion. Here P.R. Ram has traced the growth of Hinduism and Hindutva and concluded that Hinduism is a religion, while Hindutva is a political movement for upper caste hegemony based on Hinduism. He concludes by stating that, "it is to the discredit of our secular and democratic spirit that Hinduism, a religion and Hindutva a political force, appear to be a 'way of life'''. It was this article which set me thinking on what is secularism, secularization, the issues of minorities and the process of minoritisation.